Is retinal vasculature a biomarker in amyloid proven Alzheimer's disease? - den Haan, Jurre (Alzheimers Dement (Amst), 2019)
INTRODUCTION: The retina is a potential source of noninvasive vascular biomarkers for Alzheimer's disease (AD). We assessed retinal microvasculature in well-characterized AD cases, taking ophthalmological confounders into account. METHODS: We included 48 amyloid-positive AD patients and 38 amyloid-negative cognitively normal control subjects. All participants underwent ophthalmological screening to exclude interfering ocular disease. Using a multimodal approach, we measured retinal vascular parameters, choroidal thickness, macular vascular density, and foveal avascular zone size. RESULTS: We found no disease effects on retinal vascular measures (all β′s < |0.15|, all P > .2), adjusted for confounders. Venular tortuosity was inversely associated with Fazekas score in control subjects (β −0.56, P < .01), while vessel density in the outer ring of the macula was inversely associated with Fazekas score in AD cases (β −0.64, P < .01). DISCUSSION: In conclusion, retinal vasculature did not discriminate patients with AD from control subjects, despite evident changes on clinical, neuroimaging, and cerebrospinal fluid biomarkers, challenging the use of retinal vasculature measurements as AD biomarker.